Micrografting device for testing systemic signaling in Arabidopsis. (28th April 2020) - Tsutsui, Hiroki; Yanagisawa, Naoki; Kawakatsu, Yaichi; Ikematsu, Shuka; Sawai, Yu; Tabata, Ryo; Arata, Hideyuki; Higashiyama, Tetsuya; Notaguchi, Michitaka
Summary: Grafting techniques have been applied in studies of systemic, long‐distance signaling in several model plants. Seedling grafting in Arabidopsis, known as micrografting, enables investigation of the molecular mechanisms of systemic signaling between shoots and roots. However, conventional micrografting requires a high level of skill, limiting its use. Thus, an easier user‐friendly method is needed. Here, we developed a silicone microscaled device, the micrografting chip, to obviate the need for training and to generate less stressed and more uniformly grafted seedlings. The chip has tandemly arrayed units, each of which consists of a seed pocket for seed germination and a micro‐path with pairs of pillars for hypocotyl holding. Grafting, including seed germination, micrografting manipulation and establishment of tissue reunion, is performed on the chip. Using the micrografting chip, we evaluated the effect of temperature and the carbon source on grafting, and showed that a temperature of 27°C and a sucrose concentration of 0.5% were optimal. We also used the chip to investigate the mechanism of systemic signaling of iron status using a quadruple nicotianamine synthase ( nas ) mutant. The constitutive iron‐deficiency response in the nas mutant because of iron accumulation in shoots was significantly rescued by grafting of wild‐type shoots or roots, suggesting that shoot‐ and root‐ward translocation of nicotianamine–iron complexes and/or nicotianamine is essential for iron mobilization. Thus, our micrografting chip will promote studies of long‐distance signaling in plants. Significance Statement: A number of micrografting studies on systemic, long‐distance signaling have been performed, but the technique is not yet used widely. Here, we developed a silicone‐based micrografting chip to improve the ease‐of‐use, efficiency and success rate of micrografting, even for untrained users.